Unhealed healers - Depression and suicidal tendencies of female nurses as barriers to providing assistance to individuals in suicidal crisis: a cross-sectional study - Martyna Pękacka; Tytus Koweszko; Jacek Gierus; Andrzej Silczuk (BMC Nursing)
Abstract Background/objectives Studies from various countries indicate that nurses are a professional group at increased risk of depression and suicide. Hospital work involves managing life-and-death situations and coping with physical and emotional pain and suffering alongside patients and their families. The lack of adequate mental health and trauma support can adversely affect not only the mental state of nurses, but also their ability and competence to provide support to people experiencing mental crises, including suicidal thoughts. The aim of the study was to assess the epidemiology of depression and suicidal behavior in nursing staff and to examine their competence to talk about suicide. Methods The cross-sectional study comprised 400 nurses employed in various hospital wards across Poland. Researchers utilized a demographic-descriptive questionnaire, an original questionnaire assessing competence in discussing suicidal topics, and two standardized psychometric tools: the Suicidal Behavior Questionnaire (SBQ-R) and the Patient Health Questionnaire (PHQ-9). The survey was administered via an online questionnaire. Results The study revealed that nurses are a professional group at high risk of depression and suicide. 71% of the subjects (n = 284) struggled with depression symptoms of varying severity. The highest severity of symptoms was reported among those receiving psychological support (p < 0.001) and psychiatric treatment (p < 0.001). However, these individuals demonstrated greater competence in providing assistance to people in suicidal crises compared to those who did not receive such help (p < 0.05). The use of psychological and psychiatric help was a decisive factor in whether a nurse would become a wounded healer or an unhealed healer. Conclusions Given the magnitude of mental health and suicide risks among nurses, it is imperative to implement primary, secondary, and tertiary prevention measures for both nursing staff and students preparing to enter the profession.